Substantiation of Calculation Procedure of Rigid Pavement with Reinforced Base - Yu. G. Babaskin (Наука и техника)
The paper considers problems arising due to action of transport load on cement-concrete pavement. Local soil slump with formation of cavities takes place under longitudinal joints. This actioncauses a plate vibration. In order to reinforce the construction it is proposed to arrange local fixing with cavity filling. Such method makes it possible to ensure additional plate support and due to this to reduce its vertical deformation that is proved by the calculations.